O funkcjach wybranych konstrukcji prawnych Kodeksu cywilnego na tle jedności funkcji prawa - Mróz, Teresa (Kwartalnik Prawa Publicznego, 2016)
Law and its functions should be a positive value in itself. Law, having its influence on the whole of social life, is a contribution to maintaining continuity of certain communities. It is a partial element of the whole of social, economic and political life organized in the frames of the state, or e.g. an international organization, which provides the political and economic cooperation of European countries, which the EU is. It may be assumed, that the unity of the function of law provides a functional unity of the legal system. In legal literature it is most often said about functions of law, not about its one function. Nevertheless, if we assumed the concept of a single function, it would probably be broadly understood security function, containing a number of partial functions. Different authors mention different functions of law. There are general classifications, where it is said about functions of law in relation to citizens, i.e. collectivity. There are also classifications connected with partial objectives, i.e. protective or organizational function, etc. Protective function has many aspects, such as designating the formula of justice.